(untitled) (An Nawawi, 2025)
This study was conducted to analyze the contribution of zakat and socio-economic factors to inclusive economic development in districts/cities. This study uses an inclusive economic development index variable consisting of 3 main pillars, namely the economic growth index, poverty and inequality, and expansion of access and opportunities as the dependent variable and socio-religious funds (productive zakat, zakat fitrah, infaq, and other socio-religious funds) (DSKL) which are controlled by regional socio-economic factors such as regional income, GRDP, population, and area as the independent variables. The results show that in Pillar 1 (economic growth), zakat fitrah has a significant positive effect, while other socio-religious funds have a significant negative effect, indicating that zakat fitrah contributes to inclusive growth. In Pillar 2 (poverty and inequality) and Pillar 3 (expanding access and opportunities), regional income is the only variable with a significant positive effect, confirming that the fiscal capacity of local governments is a major determinant in reducing inequality and expanding access to public services. Comparatively, the research results show that religious social funds are more sensitive to economic growth, while regional fiscal policy plays a dominant role in structural improvements in welfare. These findings emphasize the importance of synergy between fiscal policy and religious social funds in promoting sustainable, inclusive economic development.